Tagging and Redistributive Taxation - Robin Boadway; Pierre Pestieau (Queen's University, Department of Economics, 2006)
We study the optimal redistributive tax structure when the population can be disaggregated into tagged groups. We begin with the case in which the tag has no normative significance, but simply separates the population into identifiable groups with different distributions of ability-types. Under reasonable circumstances, the tax system will be more redistributive in the tagged group with the higher proportion of high-ability persons. We then extend the analysis to the case where the tag reflects differences in needs, that is, differences in the resources required to achieve a given level of utility, for example, due to a medical condition or a disability. The amount of compensation given for needs depends on whether the income tax structure is differentiated by needs groups.
Keywords: H21; H23; 330; optimal income tax; tagging; needs